Revegetasi Lahan Bekas Eksplorasi Tambang Emas Berbasis Agroforestri Tanaman Adaptif - Akbar, M. Anshari; Wahyuni, Sri; Wulandari, Miranti Nur; Sulaimansyah; Ramdani, Ilham; Qurana, Nazila (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2026)
Gold mining exploration causes extensive land degradation characterized by highly acidic pH (4.0–5.0), topsoil loss, and very low organic matter content, requiring sustainable revegetation strategies to restore ecosystem and land productivity. This research identifies local, adaptive plant species for the revegetation of former gold-mining exploration land in West Sumbawa, develops an integrated agroforestry-based revegetation system, evaluates revegetation success using a comprehensive scoring system, and designs optimal planting geometry based on topography. The method employs systematic sampling over 6.74 hectares, stratified by planting year (2021–2023), and primary data collection through vegetation inventory, plant growth measurement, health assessment, and analysis using descriptive statistics, ANOVA, Pearson correlation, and the Regulation of the Minister of Forestry P.60/2009 scoring system. Results demonstrate the gamal–mahogany agroforestry system achieved gamal survival rate of 96.3% and Mahogany 92.3%, height growth of gamal 2.5–3.0 m/year and Mahogany 3.1–3.5 m/year, increased C-organic by 105%, N-total by 167%, pH by 0.65, and P-available by 156%, with a success score of 21.8/25 in the